Quality services, students' loyalty and internationalisation practices amongst international students at public universities in Malaysia - Najimdeen, Abdulhakeem Alade (Kulliyyah of Education, International Islamic University Malaysia, 2021)
The aim of this research is to explore university quality service, student loyalty and best internationalisation practices in Malaysia from the viewpoints of international students in different public universities. The research focused on addressing the unavailability of an instrument for internationalisation practices based on the perspectives of current international students in Malaysia, and the critical factors of quality service, student loyalty and internationalisation of higher education that can be used as marketing strategies to increase international students’ satisfaction, retention and enrolment in the light of the Push-Pull Theory. A total of 2,155 international students were drawn from 10 public universities due to the disparities in the number of international students in these institutions and the Covid-19 pandemic, and the valid responses after data collection are 1,575 (1,091 males and 484 females). A survey questionnaire with four sections was developed to collect data; the first section was aimed at the demography of the students, the second section contained items on university quality service based on ServQual, the third section was about international students’ loyalty, and the last section contained the instrument of internationalisation practices developed by the researcher based on previous studies. The findings indicated a moderate level of positive perception toward the quality of service received by international students but showed an unsatisfactory level of international students’ loyalty toward their universities in Malaysia, while their perceptions of internationalisation practices are positive but need improvement. The findings also showed that there are significant positive relationships between university quality service, international students’ loyalty, and internationalisation practices. Throughout the factors of the variables investigated in this study, tangibles, empathy, assurance and satisfaction are perceived as the strongest predictors of university quality service, student loyalty and internationalisation practices. The tangibility of university quality service is also perceived to be the most valuable indicator of quality service that can influence students’ satisfaction, while the critical factors that need the most attention are empathy, reliability, satisfaction, trust, social integration and community engagement. Moreover, the study found that university quality service has positive and significant direct effects on international students’ loyalty and internationalisation practices in Malaysian public universities, and student loyalty also has a significant effect on internationalisation practices. The study also revealed that internationalisation practices have positive significant effects on both quality service and student loyalty. These results demonstrate Malaysia’s success in the aspects of the internationalisation agenda, especially in terms of the universities’ infrastructure, tangibles and mobility.